IMPACT OF CLINICAL NURSING COMPETENCIES DOCUMENTING NURSING CARE AFTER THE MANAGER'S CLINICAL SUPERVISION TRAINING - Chaterine Diana Pusung; Emiliana Taringan; Wilhemus Hary Susilo (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background. Supervision is an activity of assisting, guidance, teaching, supporting someone in completing their work under policies and procedures, how to develop new skills and a broader understanding of their work so they can do it better. Aims: This study aims to determine the effect of supervising head clinic training on the competence of implementing nurses in documenting nursing care at Hospital X North Sulawesi. Methods: involving 178 respondents divided by 134 respondents in the intervention group and 44 respondents in the control group by purposive sampling technique. Result: The results of the structural model match test showed that there was a significant influence of head nurse clinic supervision training on the level of headroom clinic supervision ability significantly with a value of t = 49.12; there is a significant influence of the ability of head nurse clinical supervision to the interpersonal headroom relationship significantly with t value = 2.75; there is an influence of the level of education and length of work on the competence of implementing nurses in documenting nursing care significantly with a value of t => 2; Simultaneously there was the contribution of the head nurse clinic supervision training, the level of headroom clinical supervision ability to the interpersonal relationship of the room head with a value of R2 = 16%; Simultaneously there are contributions of the chief room clinical supervision training, the level of head nurse clinical supervision ability, the interpersonal relationship of the head nurse with the implementing nurse, age, education level, length of work to nurse competence in documenting nursing care values ​​with R2 = 61%. Conclusion: The nursing care documentation program through IT is one of the techniques to improve the quality of nursing care services.